Comparative analysis of cardiomyopathy patients in the waiting list for heart transplantology treatment results depending on a disease etiology and a selected method of treatment - A. V. Gabriyelyan (Ukrainian Journal of Cardiovascular Surgery, 2019)
Introduction. In the paper we have conducted the efficiency evaluation of complex correction of heart pump function for patients with congestive heart failure (CHF) and patients with decreased left ventricular contractility being in the waiting list for heart transplantation, with continued 1-year long prospective observation.Purpose. To analyze the treatment results of patients with cardiomyopathy being in the waiting list for heart transplanta-tion depending on disease etiology and conducted method of treatment.Materials and Methods. We have reviewed the results of 1-year prospective observation, including 166 patients with CHF against the background of Ischemic Cardiomyopathy (ICMP) (113 p.) or Dilated Cardiomyopathy (DCMP) (53 p.), being in the waiting list for heart transplantation. In the DCMP group, the Batisa left venticuloplasty (33 p.) and Cord Blood Stem Cells Transplantation (CBSCT (20 p.) transplantation has been performed. In the ICMPIC group 38 patients went through Coronary Artery Bypass Grafting (CABG), 35 – Coronary Artery Stenting (CAS), 20 patients in addition to revasculariza-tion, went through CBSCT. The separate group of 20 people with the conservative therapy has been designated. Statistical data processing has been carried out.Results and Discussion. Conducting the surgical correction of heart pump function for patients with ICMP, survival rate over the 1 year increased 1.636 and 1.667 times when conservative treatment supplemented with surgical one (CABG and CAS), and 6.0 times when conservative treatment supplemented with CABG. The effectiveness of complex therapy ICMP with the addition of Stem Cells has been revealed, 10% decrease of cardiovascular and general mortality has been proved over the group with conservative therapy, 18.9% mortality decrease compared to CABG, 18.6% – compared to Stenting. It has been proved, that 1-year mortality over the patients with DCMP decreases 15% while supplementing conservative treat-ment with CABG. On the other hand, the Batisa left venticuloplasty 1-year mortality results were unsatisfactory.Conclusion. Complex differentiated approach towards the correction of left ventricular heart pump function for patients with different forms of Cardiomyopathy facilitates a likely decrease of CHF, increase of myocardium contractility, improve patient quality of life and can be used as a bridge to heart transplantation.